Development of a Digital Reference Book for the Audio Media Course: Pengembangan Buku Referensi Digital pada Mata Kuliah Media Audio - Putra, Hamda Kharisma (Politeknik Assalaam Surakarta, 2025)
The Audio Media course in the Educational Technology Study Program plays a significant role in enhancing the effectiveness of learning. Audio media such as podcasts, lecture recordings, and interactive materials offer variety in content delivery and enrich the learning experience through sensory exploration. The diversity of audio media formats also allows information to be delivered in ways that accommodate various student learning styles. With ongoing technological advancements, research and development activities are crucial to identify current trends, technologies, and teaching methods. As part of efforts to support the learning process, a reference book was developed in the form of an e-book accessible via Android devices. This development follows a Research and Development (R&D) approach, based on the perspective of Borg and Gall, who state that this approach is effective in designing and validating educational products. The e-book development went through several stages: analysis, design, and development. The analysis stage was conducted to identify student needs, while the design stage focused on creating an engaging product that enhances learning outcomes. The development stage involved product feasibility testing using a 100-point rating scale. Validation results showed that the e-book is highly feasible for use. From the content expert validation, a score of 87.1 was obtained across 8 assessed aspects. Meanwhile, the media expert validation yielded a score of 84.1 across 12 aspects. Field testing revealed that 90% of students found the module easy to understand, 85% stated that the material was presented clearly and systematically, and 80% appreciated the visual design and illustrations in the module. Based on these results, the Android-based e-book is expected to serve as an effective learning resource that supports the advancement of learning in the Audio Media course.